Exploring a rural English teacher’s lived experiences of assessment practices in a blended learning enactment: A narrative inquiry - Haris Sugianto (Lembaga Penelitian Universitas Swadaya Gunung Djati Cirebon, Indonesia, 2022)
Although extensive studies have put a focus on the enactment of blended learning in English as a foreign language (EFL) classroom, there is a paucity of research into the teacher’s lived experiences of how they enact assessment in the blended learning activities. To fill such gap, this paper reports on a narrative inquiry of an EFL teacher’s lived experiences of conducting assessment during blended learning in the pandemic era. The study’s findings shed light on the ineffectiveness of the assessment practice during the blended learning enactment, particularly in the context of rural schools. Albeit the participating teacher in this study was fully engaged to conduct assessment from his past experiences, two major problems hinder such a practice: students’ unsubmitted assignments and poor Internet connection. Based on these findings, teachers are encouraged to find an alternative assessment practice during the blended learning, such as portfolio assessment. This suggestion is anchored by the fact that the assessment practice was not technically assisted during the blended learning activities.